Solar and galactic cosmic rays and the interplanetary magnetic field, 28 January-25 February 1967 - Lindgren, S. (1970)
Solar and galactic cosmic rays interactions with interplanetary magnetic field 28 January-25 February 1967 based on Explorer 33 and 28 satellite observations